Comparing Bile and Urine Samples as Morphine Detectors in Corpses .......... IJMTFM (2011) 1(1): 12-16 - Solhi, Hassan; Kazemifar, Amir Mohammad; Khoddami Vishteh, Hamid Reza; Badakhshan, Daruosh (International Journal of Medical Toxicology and Forensic Medicine, 2012)
Introduction: The present study aims to compare bile and urine samples of a corpse for detection of morphine. Methods: In this cross-sectional study, forensic examination of the bodies placed 59 of the 366 referred corpses at the high suspicion of opioid overdose. Urine and bile samples of the bodies were analyzed for morphine using thin layer chromatography. Results: All samples were taken from male bodies. There were no urine samples in four corpses (7%) and two urine samples (3%) produced negative results. In the remaining 53 cases, 14(24%) turned out 1+, 29(49%) turned out 2+, 8(14%) bodies turned out 3+ and 2(3%) corpses produced 4+. On the other hand, all bile samples produced positive results, in which 3(5%) turned out 1+, 20(34%) turned out 2+, 22(37%) bodies turned out 3+ and 14(24%) corpses produced 4+. The Spearman coefficient for positive urine or bile samples was 0.377(P = 0.005). Conclusion: The results of the present study show that the concentration of detected morphine in bile is greater than that of urine. Therefore, a bile sample can contribute to the detection of opioid in the corpses, especially when urine samples are not available or are negative. Keywords: Opioid, Morphine, Urine, Bile, Corpse